2014
DOI: 10.3233/nre-141177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol-dexmedetomidine combination on ischemia reperfusion-induced cerebral injury

Abstract: BACKGROUND: Due to the lack of efficient neuroprotective therapies, the ischemia-reperfusion (I/R) injury is a major medical problem urgently needed to be further studied. OBJECTIVE: To investigate the neuro-protective effects of propofol-dexmedetomidine (dex) combination on I/R-induced cerebral injury and potential mechanisms. METHODS: Sprague-Dawley rats were randomized to sham-operated, I/R, I/R plus propofol, I/R plus dex, and I/R plus propofoldex combination group. I/R insult was induced by 2 h middle cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
1
18
0
1
Order By: Relevance
“…Numerous anesthetics are used for cancer surgery, such as propofol, remifentanil and sevoflurane (26,27); however, their effects on the potential behaviors of cancer remain unknown. Propofol is an anesthetic agent that exerts numerous anesthetic, neuroprotective and myocardial-protective effects (18,28,29). Previous studies have demonstrated an association between propofol use and antitumor effects (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous anesthetics are used for cancer surgery, such as propofol, remifentanil and sevoflurane (26,27); however, their effects on the potential behaviors of cancer remain unknown. Propofol is an anesthetic agent that exerts numerous anesthetic, neuroprotective and myocardial-protective effects (18,28,29). Previous studies have demonstrated an association between propofol use and antitumor effects (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane (Iso) exerted neuroprotection by reducing the expression of the TLR4-mediated NF-κB signalling pathway and alleviating microglial activation after cerebral I/R injury in vitro and in vivo [ 21 ]. In addition, perioperative treatment with propofol (Pro) and Dex significantly suppressed cerebral I/R injury and upregulation of TNF-α and IL-1β in rats [ 22 ]. Thus, we hypothesised that there might be a link between Dex-induced spinal cord neuroprotection and both TLR4 activity and microglial activation.…”
Section: Introductionmentioning
confidence: 99%
“…Dexmedetomidine (Dex), a highly selective α 2 -adrenoceptor agonist, previously provided neuroprotection against ischemia reperfusion-induced cerebral injury ( 20 , 21 ), transient spinal ischemia ( 22 ) and isoflurane-induced neuroapoptosis ( 23 ). However, the underlying mechanisms of these processes have not been fully determined.…”
Section: Introductionmentioning
confidence: 99%